Effect of different exercise intensities on oxidative stress markers and antioxidant response in trained cyclists - Muñoz, D.; Olcina, G.; Timon, R.; Robles, M. C.; Caballero, M. J.; Maynar, M. (The Journal of Sports Medicine and Physical Fitness, 2010)
Traditionally, physical activity has been associated with beneficial effects on the organism. However, exercise has been shown to increase the production of reactive oxygen species (ROS) to a point that can exceed antioxidant defences, causing oxidative stress. Characteristics of exercise such as the intensity or duration seem to be associated with oxidative damage. The aim of this study was to evaluate the effect of exercise of two different cycling intensities on oxidative stress and antioxidant response in trained males. Twenty male trained cyclists participated in this study. The maximal exercise test consisted of an incremental cycling test until voluntary exhaustion, and the submaximal test was a steady state at 75% VO2max for 30 min on a cycloergometer. In maximal exercise test (16±4 min of cycling), the results showed an increase in malondialdehyde (MDA) from 40.6±2.0 to 45.4± 18.4 mM (p<0.05) in plasma and from 0.21±0.10 to 0.23±0.12 mmol/g Hb (P<0.05) in erythrocytes, also vitamin C increased in plasma from 3.80±1.60 to5.20±2.16 mg/mL (P<0.05) and it decreased from 130.5±34.7 to 83.4±30.0 mg/g hemoglobin (P<0.05) in erythrocytes, whereas there were no changes in vitamin E concentrations. In submaximal exercise, no significant differences were obtained in MDA, vitamin C or vitamin E. In conclusion, short time of high intensity cycling leads to oxidative stress increasing plasma and decreasing erythrocyte vitamin C levels.